2022
DOI: 10.1155/2022/2431976
|View full text |Cite|
|
Sign up to set email alerts
|

CKS2 and S100A12: Two Novel Diagnostic Biomarkers for Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic systematicness autoimmunity disease with joint inflammation. RA etiology is still unknown. Early and exact diagnosing is still hard to reach. In the paper, we purposed to discover novel diagnosis biological marker for RA. Two open, usable gene expression profiles of human RA as well as controlled specimens (dataset GSE17755 as well as GSE93272) were downloaded from the GEO database. Differentially expressed genes (DEGs) were screened between 331 RA and 88 control samples.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…S100A12 induces the production of in ammatory cytokines and recruits immune cells to the site of in ammation. As a result, the concentration of this protein in the serum and synovial uid of RA patients increases and is used to monitor the disease [27][28][29][30][31]. Also, the RAGE receptor is located on the heart and blood vessels, and S10012, by binding to it, causes the production of in ammatory cytokines and the ltering of macrophages to the vessel wall, which eventually leads to cardiovascular disorders [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…S100A12 induces the production of in ammatory cytokines and recruits immune cells to the site of in ammation. As a result, the concentration of this protein in the serum and synovial uid of RA patients increases and is used to monitor the disease [27][28][29][30][31]. Also, the RAGE receptor is located on the heart and blood vessels, and S10012, by binding to it, causes the production of in ammatory cytokines and the ltering of macrophages to the vessel wall, which eventually leads to cardiovascular disorders [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] What more,CKS2 is not only abnormally expressed in tumors, but also regulates genesis and growth, proliferation, apoptosis, invasion and metastasis of tumors, such as thyroid papillary cancer, [6] hepatocellular carcinoma, [7] cholangiocarcinoma, [8] esophageal squamous cell carcinoma, [5] breast cancer. [9] CKS2 is also expressed at high levels in numerous inflammatory conditions, such as rheumatoid arthritis, [10,11] spinal cord injury. [12] So far, various CKS2 researches have been carried out, but the specific function and potential mechanisms still largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…CKS2 is also expressed at high levels in numerous inflammatory conditions, such as rheumatoid arthritis, [ 10 , 11 ] spinal cord injury. [ 12 ] So far, various CKS2 researches have been carried out, but the specific function and potential mechanisms still largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%